ANALISIS PARAMETER OPTIMUM PENYERAPAN KATION ZN(II) OLEH BIOMASSA Hydrilla verticillata - Meyrina Eka Putri (Widyariset, 2014)
Hydrilla verticillata has a functional group that has free electrons. If the functional group is contacted with a solution containing heavy metals, it will form a bond with the metals. This study aims to determine the uptake ca- pacity of Hydrilla verticillata biomass in optimum condition and its reaction kinetics using measurement methods Atomic Absorption Spectrophotometer (AAS). Based on the research that has been done, the optimum conditions of Zn2+ cation absorption by Hydrilla verticillata biomass is at pH 5, its contact time is 120 minutes, and its maximum absorption capacity is 125 ppm. The order reaction Zn2+  cation absorption by Hydrilla verticillata biomass is 1.